ANALISIS IKLAN, PROMOSI PENJUALAN DAN KUALITAS PRODUK PADA IMPLUSE BUYING DI SOSIAL MEDIA FACEBOOK : Advertising; Sales Promotion; Product Quality; Impulse Buying - Sihombing, William (Managament Insight: Jurnal Ilmiah Manajemen, 2023)
The purpose of this study was to analyze the effect of advertising, sales promotion and product quality on impulse buying on the Facebook social media application. This research is a quantitative research and is a case study that explains the relationship between one variable and another. the subject of the population consists of several members of the population and the number of samples is 75 respondents. This study proves that advertising and sales promotion significantly affect the occurrence of impulse buying, while product quality has no significant effect on the occurrence of impulse buying. The benefits of research can be used as a reference source for companies or individuals to use Facebook ads to advertise products or services.